MODEL PERTUKARAN PADA MASYARAKAT NUSANTARA KUNA KAJIAN (PENGUJIAN) ARKEOLOGIS - Bugie Kusumohartono (BRIN, 1995)
Reciprocal exchange is the obligation of giving and receiving between individuals with different social relationships. Meanwhile, the so-called redistribution exchange is related to the obligation to pay for goods and services to community leaders (for example: kings, heads, priests), who then share some of the proceeds either for public interest or as gifts for someone. Apart from the reciprocal exchange and redistribution models, it is possible for traditional societies to apply traditional market exchange models. In this system, the perpetrators do not have certain social ties which oblige them to make exchanges and bargaining is possible in it.